Effect of silica fertilization on unconventional vegetables - Oliveira, Luís Cláudio Pessoa; Souza, Douglas Correa de; Silva, Luis Felipe Lima e; Guerra, Thiago Sampaio; Resende, Luciane Vilela; Silva, Maria Ligia de Souza (Revista de Ciências Agroveterinárias, 2020)
The objective of this work was to verify the capacity of unconventional vegetables to accumulate silicon, as well as their response to silicate fertilization. The experiment was conducted in a greenhouse in 2016. Two doses of silicate fertilization (0 and 50 mg dm-3 of Si) and nine species of unconventional vegetables (Maranta arundinacea L., Rumex acetosa L., Amaranthus spinosus L., Amaranthus viridis L., Amaranthus retroflexus L., Amaranthus deflexus L., Amaranthus hybridus L., Stachys byzantina K. Koch and Sonchus oleraceus L.) were evaluated, arranged in a completely randomized design in a 2 x 9 factorial scheme, with four replicates. The fresh and dry masses and the Si content were determined in all the plants. The unconventional vegetable species evaluated have the potential to accumulate silicon through element fertilization. The application of 50 mg dm-3 of Si provided higher Si content in the studied species. Fertilization with Si does not generally influence plant biomass.